2022
DOI: 10.3389/fmicb.2022.913624
|View full text |Cite
|
Sign up to set email alerts
|

2′-Fucosyllactose Increases the Abundance of Blautia in the Presence of Extracellular Fucosidase-Possessing Bacteria

Abstract: Blautia is a genus of anaerobic bacteria that is widely distributed in the mammalian gut. Recently, an increasing body of research has demonstrated a link between this genus and human health, suggesting applications as a novel probiotic strain. Moreover, we have previously shown that 2′-fucosyllactose (2′-FL), a major component of human milk oligosaccharides, increases the relative abundance of Blautia sp., particularly Blautia wexlerae, in the cultured fecal microbiota of healthy adults using a pH-controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…B. obeum and R. gnavus produce propionate via the propanediol pathway starting from fucose, a major constituent of 2'-FL [50]. The involvement of this pathway is further corroborated by the earlier observation that 2'-FL stimulatesBlautia species in presence of extracellular fucosidase-possessing bacteria [51]. R. gnavus has been shown to be the exclusive Lachnospiraceae representative in 2 month-old breastfed infants [52], further suggesting a key role of this species and the propanediol pathway in HMO fermentation.…”
Section: Discussionmentioning
confidence: 56%
“…B. obeum and R. gnavus produce propionate via the propanediol pathway starting from fucose, a major constituent of 2'-FL [50]. The involvement of this pathway is further corroborated by the earlier observation that 2'-FL stimulatesBlautia species in presence of extracellular fucosidase-possessing bacteria [51]. R. gnavus has been shown to be the exclusive Lachnospiraceae representative in 2 month-old breastfed infants [52], further suggesting a key role of this species and the propanediol pathway in HMO fermentation.…”
Section: Discussionmentioning
confidence: 56%
“…60 From in vitro co-culture assays, Blautia, and particularly Blautia wexlerae, has been reported to utilize fucose released from 2'-FL by Bifidobacterium bifidum, which 2'-Fucosyllactose and intestinal microbiota www.soci.org possessed extracellular GH95 ⊍-L-fucosidase. 60 In this study, the abundance of Megasphaera, a common lactate-utilizing bacteria in the gut, was increased in the FOS group, which could convert lactate to propionate through the acrylate pathway. 51 A previous study reported that, under carbon-limited steady-state conditions, lactate was converted to butyrate rather than propionate by Megasphaera.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, 2'‐FL fermentation increased the abundance of the genus Blautia in the jejunum, suggesting that Blautia might be a specialized degrader of 2'‐FL. It is reported that fucose from the degradation of 2'‐FL by the microbiota was released into intestinal tract as substrates mediating the growth of Blautia 60 . From in vitro co‐culture assays, Blautia , and particularly Blautia wexlerae , has been reported to utilize fucose released from 2'‐FL by Bifidobacterium bifidum , which possessed extracellular GH95 α ‐ l ‐fucosidase 60 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The capability of removing α- l -fucosyl residues from free oligosaccharides and glycoconjugates conferred fucosidase-possessing microbes a competitive advantage in mucin glycan foraging [ 14 ], and in turn help maintain intestinal homeostasis [ 76 , 77 ]. Fucosidases from commensal bacteria also play a role in cross-feeding with other members of the gut microbiota [ 78 , 79 ] or enteric pathogens such as Salmonella enterica serovar Typhimurium, Clostridium difficile , [ 80 ], Campylobacter jejuni [ 81 , 82 ] and other pathogens [ 83 ] facilitating their infection. Recently, α- l -fucosidases from the GH29 family were identified and characterised from the metagenome of faecal samples of breastfed infants.…”
Section: Insights Into the Biological Role Of Microbial Fucosidasesmentioning
confidence: 99%